Child labor and health in a public market, valencia, venezuela (2010)
Objectives This study was aimed at determining the living conditions, work practices, health effects and associated occupational risk factors in children working in a public market in Valencia, Venezuela.Methodology A questionnaire was administered which included demographic and exposure variables; a descriptive analysis was then made of the data. Forty-four children were selected. Results The average workday lasted 9.2 ± 3.2 hours/day. Children were most frequently employed in selling provisions and fruit (43.2 %); 22.7 % of them were evidently backward at school. The symptoms most reported were headache (84%), stress (59.1 %) and fatigue (58.2 %). Occupational accidents were reported by 11.4 % of the children and 2.3 % had suffered an occupational disease related to their present activity. The most frequently occurring occupational risks were discomfort caused by heat (93.2 %), noise (88.6 %) and repetitive work (84.1 %). A significant, indirect correlation was found between age and stress (p=0.04), as in publications showing that the negative impact of stress is more severe in children aged less than 10. It was determined that being a minor had greater significant association with the occupational risk of having greater exposure to organic toxic waste (p=0.017) and working under pressure (p=0.04). Conclusions There is no systematic data collection programme for assessing child labour in Venezuela even though a variety of risk factors have been identified and perceived for children. More sensitive indicators are required for the early identification of effects and how to control exposure to the risks mentioned above so that the problem can be studied in greater depth.